Motor Skills of 5-Year-Old Children: Gender Differences and Activity and Family Correlates. Issue 2 (April 2020) - Matarma, Tanja; Lagström, Hanna; Löyttyniemi, Eliisa; Koski, Pasi
It is unclear why there may be gender differences in the motor skills of same aged children. We compared motor skill competence of 5-year-old boys and girls ( n = 712) and examined whether variations in time spent in different types of activities and in family-related variables were associated with motor skills. We measured motor skills with the Bruininks–Oseretsky Test, Second Edition short form, and we used parental questionnaires to measure behavioral and family-related variables. Girls outperformed boys on most motor skills tasks, as eight of 14 tests showed statistically significant gender differences ( p < .001). In addition, drawing or doing handicrafts for 60 minutes or more per day was positively associated with fine motor control ( p < .001). Father's higher education was associated with the children's better body coordination ( p = .020). Finally, both attending day care ( p = .017) and outdoor physical activity for 60 minutes or more per day ( p = .034) were positively associated with strength and agility. We found no associations between manual coordination and either daily activities or family-related variables. Time spent in different activities of young children should be recognized as a means of enhancing the development of fundamental motor skills.